Factor Analysis of the Classroom Management Attitude Scale: Dimensions of Teacher Perspectives - Dr. Ayesha Saleem; Dr. Farah Fida; Yaar Muhammad (Indus Journal of Social Sciences, 2025)
This study used exploratory factor analysis to determine how the Classroom Management Attitude Scale (CMAS) functions as a whole. The CMAS evaluates teachers’ attitudes and approaches toward various aspects of classroom management in Pakistan. The research team obtained responses from 500 teachers working in different school environments. Several statistical tests were conducted to study how well the scale measures what it intends to measure. The sampling adequacy score KMO .967 confirms an excellent sampling adequacy for factor analysis. The Test of Sphericity by Bartlett confirmed that the correlation matrix was suitable (p < .001) for factor analysis. Our analysis used principal axis factoring with oblimin rotation to find latent constructs. The analysis retained factors based on scree plot results and only selected factors with an eigenvalue above 1. Through analysis, our team identified five key areas, which explained 83.179% of all variations. Extracted factors were: Five key factors outline teacher classroom management attitudes: (1) Instructional Planning and Organization, (2) Behavioral Management Strategies, (3) Student-Teacher Relationships, (4) Classroom Climate and Environment, and (5) Technology and Resource Management. Factor loadings exceeding .40 were considered significant. The study reviewed communalities along with the factor correlation matrix to see how well items reflected their assigned factors and how these factors worked with each other. The current factor structure helps us understand classroom management attitudes’ multidimensional nature while helping design effective professional development for teachers. Next research studies need to validate this factor structure across different groups and study how it can be effectively used in school education settings.